The Effect of Game-Based Learning on Understanding Binning in Grade 1 Students - Chica Awaliyah; Dinda Oktaviana; Frysca Amanda Putri; Shalwa Rizkya Salsabila; Deti Rostika (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study reviews how the Effect of Game-Based Learning on Understanding Binning in Grade 1 Elementary School Students. This study aims to describe the stages of planning, implementation, observation and reflection in the learning process of binning in grade 1 elementary school students. This type of research is Classroom Action research (PTK) which is carried out to determine learning outcomes, student creativity, which implements game-based learning on binning materials.